2009
DOI: 10.1038/jid.2008.380
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor and Coactivators SRC2 and 3 Regulate Epidermis-Specific Sphingolipid Production and Permeability Barrier Formation

Abstract: The vitamin D receptor (VDR) is a nuclear hormone receptor that controls transcription of target genes. It exerts its biological effects through transcriptional coactivators. Previously, we identified two distinct classes of VDR coactivators, VDR-interacting protein (DRIP) and steroid receptor coactivator (SRC) at different stages of keratinocyte differentiation. Here, we determined the functions of VDR and coactivators in lipid production and permeability barrier formation. Silencing of either VDR, SRC2, or S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 43 publications
1
82
0
5
Order By: Relevance
“…Additionally, 1,25(OH) 2 D regulates the processing of the long-chain glycosylceramides essential for lipid barrier formation. Oda et al [23 ]have shown that VDR knockout mice display a defective permeability barrier due to the reduced production of glucosylceramide and its decreased transport into the lamellar bodies, resulting in a lower lipid content in these bodies. …”
Section: Role Of Vitamin D In Skin Physiologymentioning
confidence: 99%
“…Additionally, 1,25(OH) 2 D regulates the processing of the long-chain glycosylceramides essential for lipid barrier formation. Oda et al [23 ]have shown that VDR knockout mice display a defective permeability barrier due to the reduced production of glucosylceramide and its decreased transport into the lamellar bodies, resulting in a lower lipid content in these bodies. …”
Section: Role Of Vitamin D In Skin Physiologymentioning
confidence: 99%
“…The expression of components of this complex decrease with differentiation, in association with an increase in Src3 [8]. This latter coactivator is important for the actions of 1,25(OH) 2 D on induction of differentiationspecific markers in keratinocytes and in the synthesis of lipid components of the epidermal barrier [10]. Of note, silencing of Src3 and VDR ablation have similar effects on the lipid barrier, suggesting that this coactivator is essential for the actions of the VDR on lipid barrier formation.…”
Section: Coactivatorsmentioning
confidence: 96%
“…While this is not accompanied by a gross epidermal defect, the CYP27B1-null mice exhibit an increase in transepidermal water loss and impaired recovery of barrier function following acute barrier disruption. 1,25(OH) 2 D also contributes to barrier function by regulating the synthesis of lipids that play a critical role in permeability barrier formation [10]. The impaired barrier function observed in the VDR-null mice is also associated with a decrease in the synthesis of glucosylceramides and altered barrier lipid composition in vivo.…”
Section: Barrier Functionmentioning
confidence: 99%
“…Эти два сигнальных пути также регулируют продук-цию гликозилцерамидов, входящих в состав липидного барьера кожи, причем зависимо друг от друга, так как нарушение одного из путей не может быть восполнено за счет другого [17][18][19]. Еще одним примером взаимной зависимости этих путей является образование комплек-са Е-кадгерин/катенин, обеспечивающего межклеточную адгезию и участвующего в регуляции дифференцировки кератиноцитов [20].…”
Section: витамин D и кожаunclassified